Smart pH-responsive polyhydralazine/bortezomib nanoparticles for remodeling tumor microenvironment and enhancing chemotherapy. (September 2022) - Wang, Rui; Xu, Xiaodan; Li, Dongdong; Zhang, Wei; Shi, Xueying; Xu, Hongxia; Hong, Jianqiao; Yao, Shasha; Liu, Jiwei; Wei, Zhenli; Piao, Ying; Zhou, Zhuxian; et al.
Abstract: The clinical translation of nanomedicines has been impeded by the unfavorable tumor microenvironment (TME), particularly the tortuous vasculature networks, which significantly influence the transport and distribution of nanomedicines into tumors. In this work, a smart pH-responsive bortezomib (BTZ)-loaded polyhydralazine nanoparticle (PHDZ/BTZ) is presented, which has a great capacity to augment the accumulation of BTZ in tumors by dilating tumor blood vessels via specific release of vasodilator hydralazine (HDZ). The Lewis acid-base coordination effect between the boronic bond of BTZ and amino of HDZ empowered PHDZ/BTZ nanoparticles with great stability and high drug loading contents. Once triggered by the acidic tumor environment, HDZ could be released quickly to remodel TME through tumor vessel dilation, hypoxia attenuation, and lead to an increased intratumoral BTZ accumulation. Additionally, our investigation revealed that this pH-responsive nanoparticle dramatically suppressed tumor growth, inhibited the occurrence of lung metastasis with fewer side effects and induced immunogenic cell death (ICD), thereby eliciting immune activation including massive cytotoxic T lymphocytes (CTLs) infiltration in tumors and efficient serum proinflammatory cytokine secretion compared with free BTZ treatment. Thus, with efficient drug loading capacity and potent immune activation, PHDZ nanoparticles exhibit great potential in the delivery of boronic acid-containing drugs aimed at a wide range of diseases.